Appendix 2 Faunal remains (Scottish Historical and Archaeological Internet Reports, 2011)
This section comprises a detailed specialist report. A total of 2080 specimens came mostly from medieval ditches, along with well stratified medieval and post-medieval layers. The assemblage is dominated by cattle, although this includes horn cores which are linked to craft activities rather than natural consumption. If horn cores are excluded sheep/goat is the most abundant species. Horse, bird and fish were also present.